Pengaruh Profitabilitas dan Leverage Terhadap Nilai Perusahaan Pada PT Energi Mega Persada Tbk - Rahman, Arif; Alwi, Alwi; Mukhlis, Mukhlis (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to analyze the effect of profitability proxied by Net Profit Margin (NPM) and leverage proxied by Debt to Equity Ratio (DER) on firm value proxied by Price to Book Value (PBV) in PT Energi Mega Persada Tbk for the period 2014–2023. This research employs a quantitative approach using multiple linear regression analysis. Data were obtained from the company’s annual financial reports published on the Indonesia Stock Exchange and the company’s official website. The classical assumption tests indicate that the regression model is free from normality, multicollinearity, heteroscedasticity, and autocorrelation issues, making it feasible for further analysis. The empirical findings reveal that NPM has a positive and significant effect on PBV, while DER also shows a positive and significant effect on PBV. Simultaneously, both variables strongly influence firm value with a coefficient of determination of 92 percent. These results confirm that profitability and capital structure are crucial factors shaping investor perceptions of energy firms’ value. This study contributes theoretically to strengthening financial literature on firm value determinants and provides practical implications for management and investors in making strategic decisions.